Labor Absorption of the Manufacturing Industry Sector in Indonesia - Novia Dani Pramusinto; Akhmad Daerobi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The manufacturing industry plays a very important and strategic role in contributing Gross Domestic Product (GDP) to the national economy and labor absorption. This study is aimed at analyzing factors influencing labor absorption of the manufacturing industry sector in Indonesia. This study employs the panel data regression analytical method of secondary data to calculate and analyze how significant are those factors influencing the labor demand of the manufacturing industry sector in Indonesia. It is found that wage, the number of industrial company, Gross Regional Domestic Product (GRDP), investment value, technology, and education variables have a significant influence on labor absorption. Partially, wage variable has a negative and significant influence on labor absorption. The number of industrial companies, regional gross domestic product, and technology variables have a positive and significant effect on it. On the other hand, investment value and education variables have no significant effect on labor absorption. The result of this study is expected to be taken into consideration in determining policies related to the process of industrialization and industrial the development suited to the related phenomena to improve the labors’ better standard of living.